2016
DOI: 10.1136/emermed-2015-205302
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-care lung ultrasound in young children with respiratory tract infections and wheeze

Abstract: Among children with respiratory tract infections and wheeze, a positive LUS seems to distinguish between clinical syndromes by ruling in pneumonia and ruling out asthma. If confirmed in future studies, LUS may emerge as a point-of-care tool to guide diagnosis and disposition in young children with wheeze.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(98 citation statements)
references
References 25 publications
2
94
0
Order By: Relevance
“…The significance of B‐lines, artefacts that appear in healthy lung, was first studied by Lichtenstein in 1997, which linked the presence of multiple diffuse bilateral B‐lines to alveolar‐interstitial syndromes . In a study in non‐hospitalized patients with mild AB, Varshney suggested that B‐lines were the most common US finding . The presence of B‐lines could be therefore considered an early marker of AB.…”
Section: Discussionmentioning
confidence: 99%
“…The significance of B‐lines, artefacts that appear in healthy lung, was first studied by Lichtenstein in 1997, which linked the presence of multiple diffuse bilateral B‐lines to alveolar‐interstitial syndromes . In a study in non‐hospitalized patients with mild AB, Varshney suggested that B‐lines were the most common US finding . The presence of B‐lines could be therefore considered an early marker of AB.…”
Section: Discussionmentioning
confidence: 99%
“…58 Four studies provided interobserver agreement, with three reporting high agreement for consolidation on ultrasound (κ=0.8-0.9). [50][51][52][53][54][55][56][57][58][59] Only one study reported the interobserver agreement for chest radiography and ultrasound simultaneously; agreement for ultrasound was fair (κ=0.55) but better than that for chest radiography (κ=0.33). 58 The limitations of ultrasound include its inability to visualize the whole lung at the same time or to identify consolidation deep within the lung parenchyma.…”
Section: Incidence Of Pneumonia In Childhoodmentioning
confidence: 99%
“…These range from conditions such as respiratory distress syndrome (RDS) and transient tachypnea of the newborn (TTN) seen in the neonatal ICU [202], to others such as pulmonary contusions from trauma and chemical pneumonitis [203, 204], as well as different causes of wheezing in children [205]. …”
Section: Diagnostic Applications Of Ultrasoundmentioning
confidence: 99%